The decapod crustaceans described by C. Sankarankutty, and a replacement name for Jonesius Sankarankutty, 1962 (Crustacea: Brachyura: Domeciidae), preoccupied by Jonesius Yamaguti, 1959 (Cestoda: Cyclophyllidea: Hymenolepididae) - Low, Martyn E. Y.; Ng, Peter K. L. (Zootaxa, 2012)
The Indian carcinologist Cheruparambil Sankarankutty has published extensively on the decapod crustaceans of India and Brazil, and over the years, has described two new genera and eight new species (Sankarankutty 1962a, b, 1963, 1968, 1969, 1975; Sankarankutty & Ferreira 2000; Sankarankutty et al. 2001) (Table 1).